Simulator Interaktif Single Linked List Berbasis Step Execution untuk Mempelajari Mekanisme Penunjukan dan Pengelolaan Memori - Edison Pardengganan Siahaan (PT. Hasba Edukasi Mandiri, 2026)
The singly linked list data structure is a fundamental concept in computer science that is often difficult to understand due to dynamic memory allocation, pointers, and changes in node relationships. This study aims to design and develop an interactive desktop-based visualization software (Java Swing) that can graphically depict a singly linked list, provide step by step simulation for insert, delete, update, and traverse operations, and synchronize the visualization with highlighted line by line C code snippets. The development method follows the iterative Unified Process with four phases: Inception, Elaboration, Construction, and Transition. In the Elaboration phase, artifacts produced include fully dressed use cases, a use case diagram, system sequence diagrams (SSDs), a design class diagram, and a low fidelity wireframe user interface. Test results show that the application successfully executes all operation scenarios, including edge conditions (empty list, single node, invalid positions). The step simulation feature with commit/non commit mechanism and backward/forward navigation works as designed. The memory panel and code highlighting help clarify the relationship between C code and changes in the data structure. This application is suitable for use as an interactive learning medium in Data Structures courses, particularly on the topic of singly linked lists.